Nutrition of the elderly. - Chandra, R K (1991)
The progressively increasing number of elderly people in the Canadian population and the disproportionate expenditure on their health care has stimulated interest in prevention of common illnesses observed in this age group. It is now recognized that nutrition plays an important role in health status, and both undernutrition and overnutrition are associated with greater risk of morbidity and mortality. Nutritional problems in the elderly can be suspected if there are several high-risk factors present--for example, living alone, physical or mental disability, recent loss of spouse or friend, weight loss, use of multiple medications, poverty, and high consumption of alcohol. Physical examination, anthropometry, and measurements of serum albumin levels and hemoglobin and lymphocyte counts are simple but helpful tools in confirming the presence of nutritional disorders. The prevention and correction of nutritional problems is likely to prove beneficial in the management of common geriatric illnesses. In these efforts, it is desirable to have a team approach in which the physician, the dietitian and the nurse each have a defined interactive role. Home care support services are important adjuncts in continuing care. Nutrition should receive a greater emphasis in the training of physicians and other health professionals.